Directed evolution of the transglutaminase from Streptomyces mobaraensis and its enhanced expression in Escherichia coli. Issue 1 (2nd January 2020) - Xue, Ting; Zheng, Xuehai; Su, Xiaomei; Chen, Duo; Liu, Kui; Yuan, Xue; Lin, Ronghua; Huang, Luqiang; He, Wenjin; Zhu, Jinmao; Chen, Youqiang
ABSTRACT: Transglutaminase-catalyzed reactions can be used widely to modify the functional properties of food proteins, biopharmaceuticals and in tissue engineering. Transglutaminase-producing organisms obtained from natural screening have a low ability to produce enzymes, and the obtained enzyme generally has low activity and poor substrate specificity, which limit its industrial applications. Of 100 isolates collected from five air-dried soil samples, 20 exhibited the typical growth characteristics of Actinomycet e s . Of these 20 isolates, S-1and S-2 resulted in 0.47 and 0.30 U/mL transglutaminase production, respectively. Based on phenotypic and the 16S rRNA gene-sequence data, the isolate S-1 was confirmed as Streptomyces mobaraensis . We produced Transetta (DE3)/PET-32(a)-YC2 mutants in Escherichia coli exhibiting improved MTGase activity and production from the screened microbial transglutaminase-producing strain by directed evolution of the MTGase gene using epPCR combined with construction and overexpression of the PET-32(a)-YC2. The activity of Transetta (DE3)/pET-32a-YC2 TGase (3.03 U/mL) in E. coli growth supernatant was 1.5 and 1.8-fold above that of the control Transetta (DE3)/pET-32a-MTGase strain (2.02 U/mL) and Transetta (DE3)/pET-32a strain (1.68 U/mL), respectively. Under the optimized conditions, the content of target protein and MTGase activity by the MTGase gene expression in Transetta (DE3)/pET-32a-YC2 (26.2% and 4.99 U/mL) were 2.07 and 1.65-fold greater than control through optimization of different parameters. These results suggest that directed evolution of the MTGase gene from Streptomyces mobaraensis can effectively enhance the MTGase activity and protein expression in E. coli . This method of enhanced expression of active MTGase in E. coli may be valuable for food and other industrial applications. Graphical Abstract: Numerous studies suggest that transglutaminase-catalyzed reactions can be used widely to modify the functional properties of food proteins, biopharmaceuticals and in tissue engineering. Transglutaminase-producing organisms obtained from natural screening have a low ability to ferment and produce enzymes, and the obtained enzyme generally has low activity and poor substrate specificity, which limit its industrial applications. In this work, we screened the isolate S-1 was Streptomyces mobaraensis from five air-dried soil samples according to the phenotypic and the 16S rRNA gene-sequencing. We produced Transetta (DE3)/PET-32(a)-YC2 mutants exhibiting improved MTGase activity and production from the screened microbial transglutaminase-producing strain by directed evolution of the MTGase gene using epPCR combined with construction and overexpression of the PET-32(a)-YC2. The activity of Transetta (DE3)/pET-32a-YC2 TGase (3.03 U/mL) was 1.5-fold above that of the control Transetta (DE3)/pET-32a-MTGase strain (2.02 U/mL). To further improve the yield of transglutaminase for the higher transglutaminase-producing strain generated by directed evolution of the MTGase gene, we optimized the following fermentation conditions: IPTG concentration, temperature, time and speed. Under the optimized conditions, the content of target protein and MTGase activity by the MTGase gene expression in Transetta (DE3)/pET-32a-YC2 (26.2% and 4.99 U/mL) were 2.07 and 1.65-fold greater than control through optimization of different parameters. These results suggest that directed evolution of the MTGase gene from Streptomyces mobaraensis can effectively enhance the MTGase activity and protein expression in E. coli . This method of enhanced expression of active MTGase in E. coli may be valuable for industrial applications.